Mobility and community at Mesolithic Lake Onega, Karelia, north-west Russia : insights from strontium isotope analysis - Eckelmann, Rebekka; Arppe, Laura; Tarasov, Alexey; Pospieszny, Lukasz; Ackerman, Lukas; Heyd, Volker; Gerasimov, Dmitry; Moiseyev, Vyacheslav; Fairbanks, Vanessa; Hyland, Corrie; Mannermaa, Kristiina (Springer, 2025)
This study investigates the underlying mechanisms driving the formation of the largest known burial site of the Northern European Mesolithic, Yuzhniy Oleniy Ostrov (YOO). Radiogenic strontium isotope analysis (87Sr/86Sr) was used to identify group dynamics within the cemetery and examine the site's place within local and supra-regional networks. The analysis of 57 humans and 31 animals was supported by the creation of an environmental baseline which identified four key geological zones and defines the strontium characteristics of Lake Onega. Only two individuals had strontium values indicating time spent outside of Lake Onega's northern shores, where the majority of the burial population is likely to have resided. These results suggest that the YOO cemetery predominantly served as a burial place for those with semi-permanent residence in this area, with no significant evidence for gender-based relocation patterns indicative of patri- or matrilocal residency. However, materials seem to have travelled towards Lake Onega even over great distances and the presence of the two outlier individuals suggests these exchanges also involved long-distance travel of people. Our results align with an increasing number of studies that suggest a high degree of residential stability for Late Mesolithic foraging groups relying primarily on aquatic resources, yet simultaneously places the Lake Onega community within a wider Mesolithic communication network. Peer reviewed